PERSEPSI SISWA MADRASAH DINIYAH DARUSSALAM DESA KASERANGAN KECAMATAN PONTANG PADA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Puput Puspitorini; Faojiyah Faojiyah; Rizki Kurniyanto (Gapenas Publisher, 2021)
This research aims to provide an overview of students' perceptions of online learning in the Covid-19 period and the negative impact of the spread of the virus on the implementation of learning by learners. The approach to this study is a descriptive case study. The research was conducted on the stairs from July 14 to August 20, 2021, in community service programs located in Kaserangan village of Pontang District of Serang Regency. This study presented 38 students class V in Madrasah Diniyah Darussalam as a research subject. Data is collected by conducting open interviews online through the WhatsApp app. Data analysis techniques use the Bogdan and Biklen models with data reduction, formulating sub-themes, and finding relationships between each sub-theme on each theme. The findings suggest that (1) technology is an essential key in the Covid-19 pandemic and a catalyst for learning that utilizes technology in the era of the industrial revolution 4.0; (2) the utilization of technology increases student engagement and makes learning possible anywhere and anytime; (3) online learning during the Covid-19 pandemic has not been running optimally; (4) barriers that arise in online learning are affected by gadgets and network conditions; (5) online learning harms the physical and mental of the student; and (6) the expectations of students in carrying out learning, namely the reduction of the burden of tasks, explanation of return from teachers on the material, and the emergence of learning variations